Reporting client violence - Macdonald, Grant; Sirotich, Frank (2001)
Much has been written about client violence against social workers; however, little attention has been given to reporting behavior of social workers who have been the target of such violence. The study discussed in this article documents the prevalence of client violence among a sample of social workers from a broad range of social work settings. It examines respondents' reasons for not reporting or for reporting client violence to management. A random sample of 300 social workers was mailed a questionnaire that examined these issues. A total of 171 questionnaires were returned, for a response rate of 57 percent. The majority of respondents had experienced some form of violence from clients. Approximately one-quarter of respondents indicated that they did not report an incident of violence perpetrated against them by a client. - Reproduced
Keywords: Violence; Social workers